Clinical Experience of Using Intraocular Lenses - A. D. Chernysheva; V. O. Afanasyeva (Oftalʹmologiâ)
Aim: to analyze the data obtained from using of intraocular lenses — the hydrophobic IOL Citrin and a hydrophilic IOL Aquamarine, produced by Russian company — NanOptic. Materials and methods. A total of 56 IOLs, produced by NanOptic (38 hydrophobic IOLs Citrine and 18 hydrophilic IOLs Aquamarine) were implanted. The observation period was from 3 to 12 months. The indication for phacoemulsification was age cataract. The age of the patients was 54–85. Patients before the operation were conducted basic studies. The mean uncorrected visual acuity before the operation was (UCVA) 0.121 ± 0.120 (0.001–0.3), and the mean corrected visual acuity was (BCVA) 0.187 ± 0.140 (0.001–0.6). All patients underwent standard phacoemulsification. Results. The early postoperative period was without any complications. In the postoperative period the mean UCVA in patients with “Citrine” and “Aquamarine” was 0.90 ± 0.10 (0.7–1.0) and 0.96 ± 0.07 (0.8–1.0) accordingly, and the mean BCVA was 0.94 ± 0.07 (0.8–1.0) and 0.99 ± 0.02 (0.9–1.0) accordingly. In all cases, the refraction obtained was consistent with the prediction. The error in IOL calculation was minimal and permissible. There weren’t any case of secondary cataract in patients with hydrophobic IOLs, and 3 cases of lens posterior capsule fibrosis of 1 degree in patients with hydrophilic IOLs in 3–12 months observation. The position of IOL in capsule bag was stable. Conclusions. The results of implantation of new Russian-made IOLs on the given parameters appeared to be satisfactory, that allows to recommend them for implantation in cataract surgery.